An employee empowerment model in healthcare organizations: a case study of the Iranian social security organization - Ali Sadeghinezhad; Hamdollah Manzari Tavakoli; Saeed Sayadi; Mahdi Mohammad Bagheri; Mohammad Jalal Kamali (Social Determinants of Health)
Background: Employee empowerment in healthcare organizations, which refers to providing staff with the autonomy, authority, and confidence to make decisions and take initiative in their roles, plays a crucial role in enhancing both productivity and the quality of health services. This study aims to design an employee empowerment model for the Iranian Social Security Organization to improve organizational performance.